The Use Of Social Media And Its Relationship With Vocational School Learning Outcomes - Alfrina Mewengkang; Keith Ratumbuisang; Hiskia Legesan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to determine whether there is a relationship between the use of social media and student learning outcomes at SMK Negeri 1 Tondano. This type of research uses a quantitative approach with a correlational design. This research is correlational because this research seeks to investigate the correlation between two variables. Quantitative research is a study that uses numbers to collect data and provide an interpretation of the research results. The results of the research are based on descriptive analysis that has been carried out using social media. Students of SMK Negeri 1 Tondano from 45 samples, there is a maximum value of 85 with a mean of 50.81. This means that most students use social media. In this study, it was obtained that the student learning outcomes of SMK Negeri 1 Tondano averaged 77.38 which indicated that the score was above the minimum passing criteria. Thus the Relationship between Social Media Use and Student Learning Outcomes Based on simple linear regression analysis, there is a significant negative relationship between social media use and Student Learning Outcomes.